Updates in Red Blood Cell and Platelet Transfusions in Preterm Neonates - Lopriore, Enrico (American Journal of Perinatology, 2019)
Anemia and thrombocytopenia occur frequently in preterm neonates and the majority of them require at least one blood transfusion during the first few weeks of life. However, there is no international consensus on optimal transfusion management neither for red blood cell nor for platelet transfusions, resulting in large worldwide variations in transfusion practices between neonatal intensive care units. In the past decade, several studies performed in adults, infants as well as neonates showed that restrictive transfusion guidelines are just as safe as liberal guidelines. In fact, some studies even showed that liberal guidelines could be associated with an increased risk of morbidity and mortality, suggesting that too many transfusions may have a deleterious effect. In a recent randomized trial in preterm neonates with thrombocytopenia, the liberal transfusion group (receiving more platelet transfusions) had a significantly higher rate of death or major bleeding than the restrictive group (receiving less transfusions). In preterm neonates with anemia, the available evidence is also limited and controversial. Two large randomized controlled trials (ETTNO and TOP) are currently assessing the safety and effectiveness of liberal versus restrictive red blood cell transfusions. Results of these large two studies, including the long-term neurodevelopment outcome, are eagerly awaited. Until then, reduction of anemia of prematurity by implementation of effective preventive measures, such as delayed cord clamping and minimization of iatrogenic blood loss, remain of paramount importance.
Keywords: anemia; thrombocytopenia; erythrocytes; platelets; transfusion; neonates